EFEK KURS, EKSPOR, DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI - Ade Putra Akbar; Herman Sjahruddin; Jumsiani Jumsiani; Ade Cahyaprandy Saputra; Andi Nazalia Ramadhani; Abdul Rauf Alhayra (Jurnal Bina Bangsa Ekonomika, 2023)
The topic discussed in this research is the influence of the exchange rate, exports and imports on Economic Growth in Indonesia. The data used in this research is secondary data obtained from the Central Statistics Agency in 2020-2022. The analysis used is the Radom Effect Model (REM) method. The test uses the classical assumption test model which consists of normality test, autocorrelation test, multicollinearity test and heteroscedasticity test. The results of the research are that the exchange rate variable has a negative and significant effect on economic growth, while exports and imports have a negative and insignificant effect on economic growth